Attribution of interminima changes in the global thermosphere and ionosphere. Issue 8 (1st August 2014) - Emmert, J. T.; McDonald, S. E.; Drob, D. P.; Meier, R. R.; Lean, J. L.; Picone, J. M.
Abstract We present a statistical attribution analysis of the changes in global annual average thermospheric mass density and ionospheric total electron content (TEC) between the cycle 22/23 solar minimum (which occurred at epoch 1996.4) and the prolonged cycle 23/24 minimum (2008.8). The mass density data are derived from orbital drag, and the TEC data are derived from ground‐based GPS receivers. The interminima change in mass density was −36% relative to the 1996.4 yearly average. Considering each multiplicative forcing independently, lower average geomagnetic activity during the cycle 23/24 minimum produced an interminima density change of at least −14%, solar extreme ultraviolet (EUV) irradiance forcing produced a density change of −1% to −13%, and changes in thermospheric CO2 concentration produced a density change of −5%. There was essentially no interminima change in global TEC derived from ground‐based GPS receivers or space‐based altimeters, even though past behavior suggests that it should have changed −3% (0.2 TEC units (1 TECU = 1016 el m−2)) in response to lower geomagnetic activity and −1% to −9% (0.1–0.8 TECU) in response to lower EUV irradiance. There is large uncertainty in the interminima change of solar EUV irradiance; the mass density and TEC data suggest a plausible range of 0% to −6%.